Cells and matrix alignment through micro-topographies and its influence on later lineage differentiation - Hee, Esther Xuan Yi (2015)
Challenges are constantly being encountered in the area of scaffold free tissue engineering and cell sheet engineering has been advancing to develop as an alternative approach to improve mesenchymal stem cell-mediated tissue regeneration. This interdisciplinary engineering has gained much attention due to the need to overcome the drawbacks in the current tissue regeneration due to certain diseases that cause patients to suffer in pain and losing their mobility. Therefore this leads to an increased interest in the development of biologically based repairs, to reconstruct the damaged tissues in joints using living cells that will integrate with the patient's tissues and yield a functional joint, which will benefit the patient. One of the potential solutions to it is cell sheet engineering as it has provided a platform technology for regenerative medicine in the form of single sheet or stacked arrangements of multiple cell sheets. Many studies have investigated the potential use of cell sheet for regenerative medicine but the optimization of these technologies remains unclear. One possible optimization is the controlling of the cells and matrix alignment through micro-topographies. A few studies have shown that topographies were known to affect cell proliferation, migration and differentiation. However, the use of micro-topography in cell sheet engineering has yet to be explored. A better understanding of micro-topographies has the potential to enhance the regenerative therapies. This report gives the overview on the advanced cell sheet engineering involving the array of different micro-topographies which have been created with photo and soft-lithography for cell alignment. Histological and RNA analysis had been performed to verify the presence of various proteins and to assess the level of different genes markers respectively on cell sheet and the differentiated cells, osteocytes and chondrocytes. Cell proliferation assay was performed to ensure the viability of the cell sheet in this project and Transmission Electron Microscopy (TEM) was incorporated at the end of this project as well. We demonstrated that different micro-topographies could direct the alignment of the cells and resulted in the differences in later differentiation in terms of proteins and genes marker. Therefore, based on these results, we conclude that the array of micro-topographies have the ability to influence the cell and matrix alignment. Therefore, based on these results, we conclude that the array of micro-topographies of rectangle and grill are the best designs for better cell alignments and enable the cells to express higher level of proteins and gene markers.